The incidence and risk factors of coronary steal after ipsilateral AVF in patients with a coronary artery bypass graft. Issue 4 (July 2017) - Ahn, Sanghyun; Han, Ahram; Kim, Song-Yi; Choi, Chanjoong; Min, Sang-il; Ha, Jongwon; Hwang, Ho Young; Kim, Ki-Bong; Min, Seung-Kee
Objective: Ipsilateral arteriovenous fistula (AVF) may cause symptoms of coronary steal in patients who had undergone coronary artery bypass graft (CABG) using internal thoracic artery. The purpose of this study was to evaluate the adverse effects of ipsilateral AVF to CABG, including the incidence of coronary steal, and to analyze the risk factors for coronary steal. Methods: Between 2000 and 2013, a total of 25 patients undergoing hemodialysis via upper extremity AVF, ipsilateral to the preexisting CABG, were reviewed retrospectively. Clinical assessment related to coronary steal, echocardiography before AVF, and coronary angiography after symptoms were assessed. The definition of coronary steal was the new development of one or more of the following symptoms within 12 weeks after AVF creation: chest pain, chest discomfort, and dyspnea. Results: Three patients were clinically diagnosed as coronary steal. Left ventricular ejection fraction (LVEF) was statistically lower in coronary steal group compared to no-steal group (41.7% vs. 50.9%; p = 0.036). Patients with coronary steal were older at the age of CABG surgery and showed a higher incidence of regional wall motion abnormality. Conclusions: Coronary steal after ipsilateral AVF creation in patients with CABG using in situ internal thoracic artery (ITA) developed in 12%, which can be related to low LVEF. In patients with CABG requiring AVF for hemodialysis, the ipsilateral fistula to the grafted ITA should be carefully selected and performed.